Three-dimensional Quantitative Structure-activity Relationship (3DQSAR) and Molecular Docking Study of 2-((pyridin-3-yloxy)methyl) Piperazines as α7 Nicotinic Acetylcholine Receptor Modulators for the Treatment of Inflammatory Disorders - Purohit, Deepika; Saini, Vandana; Kumar, Sanjiv; Kumar, Ajit; Narasimhan, Balasubramanian (Mini Reviews in Medicinal Chemistry, 2020)
Background & Objective: Comparative molecular field analysis (CoMFA) of 27 analogues of 2-((pyridin-3-yloxy)methyl)piperazine derivatives was carried out using software Tripos SYBYL X. Optimal r2 (0.854) and q2 (0.541) values were obtained for the developed 3D-QSAR model. The contour plots obtained from CoMFA analysis have shown 13.84% steric contribution and 66.14% electrostatic contribution towards an anti-inflammatory activity. Methods: The homology model of the receptor protein, α7 nicotinic acetylcholine, was generated in SWISS MODELLER using auto template mode and was analysed for the quality using Procheck, QMEAN Z-score, Anolea and GROMOS plots. The QMEAN score for the model was observed to be - 3.862. The generated model of alpha 7 nicotinic acetylcholine receptor was used for docking study of 27 piperazine analogues using Auto-Dock 4.2.5.1. Results: The dock score obtained from docking analysis was then correlated with experimental pIC50 values for in-silico validation of the developed CoMFA model and a good correlation was obtained with correlation coefficient (r2) value of -0.7378. Conclusion: The present investigation suggests an optimal 3D-QSAR with CoMFA model for further evaluating new chemical entities based on piperazine skeleton.
Keywords: nicotinic acetylcholine receptors